Exploring Psychological Violence in the Workplace: Implications for Mental Health and Organizational Well-being - Velásquez, Nestor Raúl Porras (Nusantara Journal of Behavioral and Social Science, 2024)
This study examines workplace violence from the perspective of occupational health psychology, focusing on its psychological impact and the development of intervention strategies. Using a historical approach, the research reconstructs the organizational discourse of violence by analyzing how subjectivity is controlled within workplace contexts through language, actions, and power dynamics. Workplace violence, including mobbing and psychological harassment, emerges as a systemic issue driven by structural and symbolic violence, deeply ingrained in organizational frameworks and supported by scientific narratives and self-regulation mechanisms. The findings indicate that such violence not only perpetuates but also institutionalizes docile work subjectivities, viewed as desirable in many organizational settings. The study provides a novel contribution by emphasizing the interplay between occupational health psychology and the broader sociocultural contexts that shape workplace interactions. It underscores the psychosocial risks posed by workplace violence to employees' mental health, organizational cohesion, and overall productivity. The conclusions advocate for comprehensive intervention strategies that address the root causes of workplace violence, promote healthier organizational environments, and reduce psychosocial risks. By integrating empirical insights and theoretical perspectives, this study offers valuable implications for policymakers, organizational leaders, and researchers seeking to mitigate the negative impacts of workplace violence.